PEMILIHAN PRESIDEN DAN TIM SUKSES (PERAN TIM SUKSES Ir.H. JOKO WIDODO – Drs.H. M. JUSUF KALLA DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN DI KOTA PEKANBARU 2014 - Tampubolon, Alexander Putra; Yusri, Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Pekanbaru is the capital of riau province that has been growing rapidly with good contruction. Pekanbaru is the basis of Deconnsentration as intended in a constition no 5 Year 1974 about principal of Government in a City. Pekanbaru consists of 12 districts. Based on the legislative election data in 2014, Pekanbaru gets 45 Chairs with 36.164 votes. From PDI-P for Jokowi as a president candidate with high popularity and electibility suscessgets 5 chairs. However, in general election Jokowi-JK is failed in all of districts in Pekanbaru. In this research the writer wants to know how is the role of Jokowi-Jk team in president election in Pekanbaru. The Purpose of this research is to find out the role Jokowi/Jk team in Pekanbaru.The location of this research will be Pekanbaru Riau province. The research uses Qualitative research methodology and the data will be collected from mass media. Last the data composed in stages for the writer in analysing.According to research finding, the writer find there are four (4) roles that Jokowi-JK team did general election to make Jokowi/Jk become the winner. They are : Mass Mobility, issue mapping, make a good political image and politics campaign. But all of thoses roles are not maximum because of the lack of money there for the result is not optimal.Keywords: the 2014 presidential election, team success